1994
DOI: 10.1128/jvi.68.11.7546-7548.1994
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus fusion: role of the cysteine-rich region of the fusion glycoprotein

Abstract: Measles virus (MV) fusion requires the participation of both the fusion (F) and hemagglutinin (H) glycoproteins. The canine distemper virus fusion protein (CDVF) cannot substitute for the measles virus fusion protein (MVF) in this process. Introduction of restriction enzyme sites into the cDNAs of CDVF and MVF by site-directed mutagenesis facilitated the production of chimeric F proteins which were tested for their capacity to give fusion when coexpressed with MVH. Fusion resulted when the amino-terminal half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…This substitution resulted in a 50% reduction in NA activity and a slight attenuation of the virus in vitro but did not affect cell-to-cell fusion. In previous studies, in vitro expression of chimeric HN proteins with segments derived from heterologous paramyxoviruses suggested that specificity for the homologous F protein is determined by the stalk domain of HN, although certain regions in the transmembrane anchor and globular head have also been reported to contribute to F protein specificity (11,26,41,47,50,51,54). The present results, which involve complete virus rather than cDNA-expressed proteins, are consistent with the stalk domain playing a major role in homologous interactions.…”
Section: Discussionsupporting
confidence: 90%
“…This substitution resulted in a 50% reduction in NA activity and a slight attenuation of the virus in vitro but did not affect cell-to-cell fusion. In previous studies, in vitro expression of chimeric HN proteins with segments derived from heterologous paramyxoviruses suggested that specificity for the homologous F protein is determined by the stalk domain of HN, although certain regions in the transmembrane anchor and globular head have also been reported to contribute to F protein specificity (11,26,41,47,50,51,54). The present results, which involve complete virus rather than cDNA-expressed proteins, are consistent with the stalk domain playing a major role in homologous interactions.…”
Section: Discussionsupporting
confidence: 90%
“…Fusion protein chimeric constructs have also further elucidated the role of the fusion protein in regulating membrane fusion. A study showed that switching an Ďł45-amino-acid residue region in canine distemper virus (CDV) F to that of a homologous MeV F region resulted in fusion when triggered by MeV H (34). In a similar study, the substitution of a different region, a central pocket, from MeV F to CDV F also induced fusion when triggered by MeV H (35).…”
mentioning
confidence: 99%
“…A number of previous studies have demonstrated that the cell fusion induced by paramyxovirus glycoproteins requires expression of both glycoproteins (3,5,7,13,21,26,32). Furthermore, the requirement for the HN protein is generally restricted to HN proteins from the same species of virus (2,3,7,11,15,34). It has been suggested that a type-specific interaction occurs between F and HN proteins and is involved in fusion activity (7,12).…”
mentioning
confidence: 99%